Differential diagnosis between urticarial vasculitis and chronic spontaneous urticaria: An international Delphi survey - Krause, Karoline (2023)
Background: Urticarial vasculitis (UV) should be differentiated from chronic spontaneous urticaria (CSU) in patients initially presenting with recurrent wheals, although criteria for differential diagnosis remain ill‐defined. Objectives: To set the goals, define criteria and unmet needs in UV diagnosis and differential diagnosis with CSU, and explore the possibility of coexistence of both diseases. Methods: Thirteen experts experienced in UV research participated in a Delphi survey of European Academy of Allergy and Clinical Immunology taskforce. This Delphi survey involved three rounds of anonymous responses to n=32 questions with the aim to aggregate the experts' opinions and to achieve consensus. Urticaria specialists (n = 130, most from Urticaria Centers of Reference and Excellence) evaluated the consensus statements and recommendations in the fourth and final round. Results: The panel agreed that essential criteria to guide a skin biopsy in patients with recurrent wheals should include at least one of the following features: wheal duration >24 h, bruising/postinflammatory hyperpigmentation, and systemic symptoms. Leukocytoclasia and fibrin deposits were identified as a minimum set of UV histological criteria. As agreed by the panel members, CSU and normocomplementemic UV (NUV) may coexist in some patients. Conclusions: The use of established criteria for the diagnosis and differential diagnosis of UV in patients with recurrent wheals can help guide the diagnostic approach and prompt earlier treatment. Further studies should investigate whether CSU and NUV are different entities or part of a disease spectrum.